PEMANFAATAN BAHAN TUMBUHAN SEBAGAI BIOKATALISATOR DALAM PRODUKSI MINYAK SAWIT KAYA ASAM LEMAK OMEGA-3 1) [Using of Plant Biocatalisator for Omega-3 PUFA -Rich Palm Oil Production] - Jenny Elisabeth; D. Siahaan; D. R. H. Simajuntak (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
Incorporaton of omega-3 polyunsaturated fatty acids (n-3 PUFA) into red palm oil was investigated by using acidolysis process. Rice bran and Carica papaya latex (CPL) were used as biocatalyst. Acidolysis between red palm oil and n-3 PUFA concentrate in free fatty acid form was conducted without solvent, with weight ratio of n-3 PUFA concentrate to palm oil being 1:1. The n-3 PUFA concentrate was prepared from tuna oil by crystallization method. The study has demonstrated that rice bran lipase showed higher activity to incorporate n-3 PUFA into red palm oil than CPL. The extent of EPA (eicosapentaenoic acid, C20:5) and DHA (docosahexaeboic acid, C22:6) incorporation were 3.4% and 12.7% with the rice bran lipase, and 1.7% and 3.2% with the CPL. Furthermore, rice bran from several varities of paddy (Mamberamo, IR-64, Merah Munte , and Cirata) produced equal incorporation of EPA and DHA into red palm oil. Rice bran from germinated seed of paddy did not increase the n-3 PUFA incorporation into red palm oil. It means that rice bran in its natural form could be used and act as immobilized lipase. It is easier to remove the rice bran from reaction mixture and reuse the bran for 14 times without decreasing its enzyme activity.